An AI based self-moderated smart-home - Assim, , Awss; Reaz, M. B. I.; Ibrahimy, M. I.; Ismail, A. F. (2006)
Smart-home conception has emerged in recent years and played a very important part in the formation of future houses. Making our current homes more adaptable and self-directed is the main focus of smart home research. Achieving these goals won't be possible without giving our today's home enough intelligence to make rational decisions to operate itself which usually we as inhabitants of the home make these decisions in our everyday life to manage our home and achieve comfort that we desire. In this paper we present prototype of a system that overcomes this problem by giving the home enough intelligence to adapt to its inhabitants life style without the need for the inhabitants to exercise authority. The system makes use of multi-agent and prediction techniques to provide intelligent smart-home appliances automation. The final prototype will be downloaded into FPGA chip.